If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 1 = 3x + -4 Reorder the terms: 1 + 5x = 3x + -4 Reorder the terms: 1 + 5x = -4 + 3x Solving 1 + 5x = -4 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 1 + 5x + -3x = -4 + 3x + -3x Combine like terms: 5x + -3x = 2x 1 + 2x = -4 + 3x + -3x Combine like terms: 3x + -3x = 0 1 + 2x = -4 + 0 1 + 2x = -4 Add '-1' to each side of the equation. 1 + -1 + 2x = -4 + -1 Combine like terms: 1 + -1 = 0 0 + 2x = -4 + -1 2x = -4 + -1 Combine like terms: -4 + -1 = -5 2x = -5 Divide each side by '2'. x = -2.5 Simplifying x = -2.5
| 6d-48=42-3d | | 11p-66=5p | | -(a-15)= | | 100+5p=60+2p | | x-2=2-3x | | 7k-49=22+2k | | (5x+2)(2x-5)=0 | | -(-9-4y)= | | g-1=5-1-9 | | -1(p+6)= | | 36y^2-1=15 | | 3.7q-1.9-3.4q=-0.7q-1.9 | | (1-11j)4= | | 3.7q-1.9q-3.4q=-0.7q-1.9 | | 7(11-n)= | | 0.3q-1.9=-0.7q-1.9 | | 12(4-8p)= | | 7+2(a-3)= -9 | | 17(2b+3)= | | 5m+5=7m-7 | | (6y-3)5= | | 3x^3-13x^2+16=0 | | (2h-4)11= | | 3t^2+4t+1=0 | | 3(2+w)= | | g(-1)=5(-1)-9 | | 4x-6x-4=0 | | 4x(x+2)-x(3+4)=2x+18 | | 7(z-4)= | | 4x^2+21x+22=-4x+4 | | 5(x-2)=8#-3 | | 12x-41+5x+5y= |